Exogenous salicylic acid alleviates oxidative damage of barley plants under drought stress - Habibi, Ghader (Acta Biologica Szegediensis, 2012)
This paper reports the effects of 500 μM salicylic acid (SA) application on drought stress acclimation of barley (Hordeum vulgare L. cv Nosrat) plants grown in soil culture. In these experiments the following treatments were used: CK (control), DR (drought), SA (500 μM) and DSA (SA+drought). The results showed that drought stress decreased the dry mass and net CO2 assimilation rate (A) of plants, which were all increased by the addition of SA. Under drought conditions, the improvement of photosynthesis of barley plants treated with SA was associated with an increase in gs, whereas the maximal quantum yield of PSII (Fv/Fm) did not change with SA treatment. Malondialdehyde (MDA) content remained unchanged in DSA plants because of an efficient scavenging of reactive oxygen species (ROS) following a significant enhancement of some antioxidative enzyme activities. The present work suggests that the improvement of SA on drought tolerance of barley plants was associated with the increase of antioxidant defense abilities and maintenance of photosynthesis under drought, which may elucidate the physiological mechanism of SA in improvement of drought tolerance of barley plants.